Pengelolaan Taman Wisata Alam Ditinjau dari Aspek Hukum Lingkungan - Muhammad Khaidir Kahfi Natsir; Ayub Jose Luhut Parulian Simanjuntak (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This paper discusses the relationship between green constitution and ecocracy in the context of environmental management in Indonesia. In the modern era, the importance of maintaining a balance between economic development and environmental sustainability has become increasingly urgent. The issues raised include the need for a deep understanding of environmental legal norms adopted in the 1945 Constitution, as well as the challenges faced in its implementation across various sectors, particularly in the management of Nature Tourism Parks. The aim of this research is to explore the role of the green constitution in supporting sustainable development and environmental protection, as well as to analyze the impact of existing policies on ecosystems and communities. The method used is a normative legal approach with descriptive analysis, involving the collection of secondary data from various literature sources, laws, and related documents. The findings indicate that although the green constitution has provided a strong foundation for environmental protection, its implementation still faces challenges, such as a lack of legal awareness among the public and inconsistent enforcement of regulations. Additionally, challenges in managing Nature Tourism Parks are often caused by increasing pressures from tourism activities that can damage ecosystems. The conclusions drawn emphasize the importance of better regulatory integration and ongoing supervision of the management of Nature Tourism Parks. This is necessary to ensure ecosystem sustainability and environmental preservation, as well as to support active community participation in maintaining environmental integrity. This research highlights that collaboration between the government, society, and other stakeholders is crucial for effectively implementing the principles of ecocracy and the green constitution.